Analysis on the application and development of quantum communication - Junsen LAI; Bingbing WU; Rui TANG; Wenyu ZHAO; Haiyi ZHANG (Dianxin kexue)
Quantum communication，which can provide unconditional security，is a physical layer solutions for information security.The status and challenge of its technology development and application are the focus of the industry.The field trials of quantum communication and main problem were analyzed.Driving force and bottleneck of its commercialization were clarified and worldwide standardization research were reviewed.System performance test and evaluation were discussed and future development recommendations were also provided.